Why Does Language Matter to Philosophy? - Hacking, Ian (London Cambridge University Press, 1975)
Many people find themselves dissatisfied with recent linguistic philosophy, and yet know that language has always mattered deeply to philosophy and must in some sense continue to do so. Ian Hacking considers here some dozen case studies in the history of philosophy to show the different ways in which language has been important, and the consequences for the development of the subject. There are chapters on, among others, Hobbes, Berkeley, Russell, Ayer, Wittgenstein, Chomsky, Feyerabend and Davidson. Dr Hacking ends by speculating about the directions in which philosophy and the study of language seem likely to go. The book will provide students with a stimulating, broad survey of problems in the theory of meaning and the development of philosophy, particularly in this century. The topics treated in the philosophy of language are among the central, current concerns of philosophers, and the historical framework makes it possible to introduce concretely and intelligibly all the main theoretical issues.
Keywords: 20th Century (1901-2000); Philosophy; Linguistics; United Kingdom